PRODUKSI FORMULASI INSEKTISIDA CAIR BENTUK EMULSIFIER CONCENTRATE YANG EFEKTIF GUNA MEMBASMI NYAMUK AEDES AEGYPTI DALAM USAHA MENCEGAH PENYAKIT DEMAM BERDARAH - Supriyo, Edy; Abidin, Zainal; Nugraheni, Nugraheni; Wahyuni, Sri (Universitas Diponegoro, 2011)
Abstract Â Liquid pesticide formulation in the form of emulsifier concentrate (EC) is more preferable because it does not form clogging and blocking in the tools and precipitating that harden. Based on fired capacity in the whole pesticide formulation industry, about 25 % produce emulsifier concentrate. In the emulsion formulation, the important point is unite insoluble matter become a homogeny and stable formulation for long period. The selection of emulsifier type is very important because it is influenced by quality and EC formulation stability. Result formula very good is 20 % propoxure; 5 % Malathion; 5 %; agrisol ; 20 % DBS; 45 % Xyline dan 5 % additive (%w/w), concentration affection test 0.025% v/v for thinner solvent in 20 strain aedes aegypti mosquitoes at Semarang killed on 2 hours = 4 mosquitoes, 4 hours = l0 mosquitoes, 6 hours = 16 mosquitoes and on 8 hours all mosquitoes had been died. From emulsion stability test, in oil phase and water phase was found terpentine as stable solvent in the emulsion form, with separated oil percentage at concentration 3mg/l about 42%. In water phase emulsion forms micro emulsion with white fog colors in whole concentration 1, 2 and 3 ppm Â Keyword: Emulsifier Concentrate